Expansion And Refurbishment Of State Realschule Schelitz. [Tender documents : T35102737] (MENA Report, 2016)
Extension (cultivation and increased approximately 13,200 m3 BRI) and refurbishment (approximately 33,600 m3 BRI) of the National Secondary School Schelitz; trades as award by subject lotsGewerk / LV 02: carpentry BA 1, extensionGewerk / LV 03: Plumbing BA 1, extensionGewerk / LV 17: lift installation BA 1, extension.